Copper deficiency in Creole goat kids - Draksler, Diana (2002)
Serum copper determination is important to confirm hypocupremia. Twenty healthy kids constituted the Control Group, and sixteen kids with symptoms of copper deficiency, the Problem Group. Animals from the Problem Group showed a low number of red blood cells (RBC) and variations in RBC size and shape. The values found for hemoglobin and mean corpuscular hemoglobin (MCH) in the Control Group were 10.42 ± 1.34 g·dL-1 and 33.07 ± 1.11 g·dL-1 respectively, while the levels of the Problem Group were 7.95 ± 1.21 g·dL-1 and 29.45 ± 0.78 g·dL-1, respectively. The kids from the Problem Group presented an important increase in monocytes, neutrophiles and leukocytes; precursor cells of the neutrophile were also observed. The anemia of these animals was hypochromic and macrocytic. Our results indicate the Creole kids with serum copper levels > 450 μg·L-1 improved after treatment with copper glycinate. The six goats with cupremia < 450 μg·mL-1 were unable to improve their deficiency and died.